2000
DOI: 10.1002/(sici)1097-010x(20000301)286:4<329::aid-jez1>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of actin and tubulin in the integument of land crab (Gecarcinus lateralis) and lobster (Homarus americanus)

Abstract: The crustacean integument consists of the exoskeleton and underlying epithelium and associated tissues. The epithelium, which is composed of a single layer of cells, is responsible for the cyclical breakdown and synthesis of the exoskeleton associated with molting (ecdysis). During premolt (proecdysis) the epithelial cells lengthen and secrete the two outermost layers (epicuticle and exocuticle) of the new exoskeleton while partially degrading the two innermost layers (endocuticle and membranous layer) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…As in this study, Mykles et al [51] detected actin in the epithelium, and membranous and endocuticular layer of crab and lobster exoskeletons. The authors suggested that the epithelium of these crustaceans secreted actin, together with tubulin to enable the incorporation of these proteins into the extracellular matrix, where the proteins could function as stabilizers or organizers of the matrix.…”
Section: Discussionsupporting
confidence: 80%
“…As in this study, Mykles et al [51] detected actin in the epithelium, and membranous and endocuticular layer of crab and lobster exoskeletons. The authors suggested that the epithelium of these crustaceans secreted actin, together with tubulin to enable the incorporation of these proteins into the extracellular matrix, where the proteins could function as stabilizers or organizers of the matrix.…”
Section: Discussionsupporting
confidence: 80%
“…Studies on rice and Arabidopsis indicated hyperosmotic stress induced α-tubulin phosphorylation [44]. Studies on land crab and lobster confirmed that tubulin localized in exoskeletal structures, it may serve both intracellular and extracellular functions in crustaceans [45]. In this study, we found that the EsTUBA mRNA expression fluctuated with the morphological changes in the brachyurization metamorphosis process of E. sinensis.…”
Section: Discussionsupporting
confidence: 54%
“…As we known, the moulting of juvenile E. sinensis principally required enough preparations of energy storage (Catacutan ), hormone concentration (Chang & Mykles ) and immune system protection (Mykles et al . ). Energy storage in juvenile E. sinensis is mainly dependent on lipid content in the midgut gland and muscles.…”
Section: Introductionmentioning
confidence: 97%
“…Based on the new cuticle formation and calcification (Sakamoto et al 2009) in the lateral spine, the postmoult phase (Freeman et al 1987) was subdivided into soft, leathery and paper shell stages. As we known, the moulting of juvenile E. sinensis principally required enough preparations of energy storage (Catacutan 2002), hormone concentration (Chang & Mykles 2011) and immune system protection (Mykles et al 2000). Energy storage in juvenile…”
mentioning
confidence: 99%